2013
DOI: 10.1016/j.jcis.2012.09.074
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cooperative unit size of amphiphilic molecules in the phase coexistence region in Langmuir monolayers

Abstract: The dependence of the size of cooperative unit (C.U.) of the amphiphilic molecules on the surface pressure () in the liquid expanded (LE) -liquid condensed (LC) phase coexistence region of Langmuir monolayers has been formulated and calculated using the measured isotherm data. The C.U. size changes largely depending on the surface pressure in the coexistence region and these submicroscopic molecular aggregates are not static objects but dynamic ones characterized by large fluctuations in size. It has been fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In Figure 2 a, it can be seen that the LE/LC phase transition of DMPC was modified by the presence of Dex, becoming less marked, but without an evident modification on the transition surface pressure. This can be explained considering a decrease in the cooperativity of the phase transition due to the presence of Dex in the monolayer [ 40 ]. For a Dex fraction of 0.7 or higher, the LE/LC phase transition is not evident from the compression isotherm.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 2 a, it can be seen that the LE/LC phase transition of DMPC was modified by the presence of Dex, becoming less marked, but without an evident modification on the transition surface pressure. This can be explained considering a decrease in the cooperativity of the phase transition due to the presence of Dex in the monolayer [ 40 ]. For a Dex fraction of 0.7 or higher, the LE/LC phase transition is not evident from the compression isotherm.…”
Section: Resultsmentioning
confidence: 99%
“…It is experimentally well known that cooperative clusters are formed in the LE-LC phase-coexistence region and that their size is normally finite (the order of 10-100 molecules) [13,15,30,31]. If this limited cooperativity is a dominant mechanism for the transition progress, the transition will certainly occur over some surface pressure range [14,22].…”
Section: Discussionmentioning
confidence: 99%
“…The isotherms, characterized by the appearance of a nonhorizontal slope region followed by a steeper nonlinear ascent region in the phase-coexistence region of a first-order liquid-expanded (LE)-liquid-condensed (LC) phase transition, have been most commonly found in some fatty-acid monolayers [6] and in phospholipid monolayers [7,8]. The origin of a nonzero slope in the isotherm has been extensively discussed from various perspectives: (i) the effect of impurities in monolayer materials [9,10], (ii) the effect of the long-range dipole interaction [11,12] and (iii) the formation of two-dimensional molecular aggregates such as surface micelles and submicroscopic clusters constituting a finite number of amphiphilic molecules [13][14][15]. Besides the above possibilities, some authors discussed the nonhorizontal slope of isotherms from certain mechanical viewpoints.…”
Section: Introductionmentioning
confidence: 99%
“…22 For the  dependence of cooperative cluster size during the transition the above study was extended to the use of the experimental integral equation that involved isotherm and compressibility data. 23 Freire and Biltonen demonstrated that the partition function of a bilayer system is experimentally accessible by means of the integral equation from scanning calorimetric data of lipid bilayers. 24 They applied a statistical mechanical deconvolution procedure based on the canonical approach to the measured specific heat to produce a lipid domain (submicroscopic cluster) distribution function in the gel-liquid crystalline phase coexistence region of the temperature-driven main transition that was consistent with the measured specific heat.…”
Section: Introductionmentioning
confidence: 99%
“…Here, it should be noted that the determination of both LE (liquid-crystalline) and LC (gel) phase boundaries is required for the estimation of the cooperative cluster size during the isothermal or isobaric transition in all the above methods. 22,23,24 Concerning the phase boundaries in the LE-LC transition the measurement of the molecular area ALE of the low density LE phase boundary can be made normally rather accurately from a break in the slope of the isotherm. We have, however, difficulty in accurately determining the high density LC phase boundary ALC, since the termination of the phase transition on compression is not clearly observed in the isotherm.…”
Section: Introductionmentioning
confidence: 99%